International best practices for evaluation in the health professions - McGaghie, William C. (Radcliffe Publishing, 2013)
This book presents a comprehensive narrative on why and how health professions students need to be evaluated for practice in the 21st century. It systematically addresses current evaluation best practices in the health professions to identify today's evaluation benchmarks, reveal evaluation limits, address improvement pathways, and map a research agenda to boost future evaluation practices. Advancements in information and communication technology, bioscience and behavioral research, and worldwide travel are dissolving barriers that have separated professions, countries, and cultures for centuries. This book also celebrates these achievements and carefully considers next steps. It recognizes the huge improvements made in evaluation practices within the health professions over the past 40 years but asks for more calling for added reform and better understanding of current practice from different social, cultural, and educational perspectives